2018
DOI: 10.1111/1467-9566.12829
|View full text |Cite
|
Sign up to set email alerts
|

Rejecting, reframing, and reintroducing: trans people's strategic engagement with the medicalisation of gender dysphoria

Abstract: This article uses ethnographic methods to explore how transgender people engage the medicalisation of transgender experience in a U.S. context under the purview of the American Psychiatric Association. Building on sociological literature related to medicalisation, this paper argues that the lived experience of medicalisation is a non‐linear, complex process whereby individual engagement with medical authority is both empowering and constraining in the lives of trans people. Inductive qualitative analysis of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 44 publications
2
65
0
Order By: Relevance
“…I was treated as a dependent who needed parents' permission even though children are able to access transition services without parents' permission here because it's a private matter. I could not even start on a low dose because I wasn't planning to change my legal gender, though I had transitioned socially.In each of these examples, we see the same patterns of cisnormativity noted by transmen and transwomen in prior literature (for reviews, see Johnson , ) also finds voice as a foreclosure of fluid possibilities in the lives of fluid people.…”
Section: Foreclosing Fluiditysupporting
confidence: 72%
See 2 more Smart Citations
“…I was treated as a dependent who needed parents' permission even though children are able to access transition services without parents' permission here because it's a private matter. I could not even start on a low dose because I wasn't planning to change my legal gender, though I had transitioned socially.In each of these examples, we see the same patterns of cisnormativity noted by transmen and transwomen in prior literature (for reviews, see Johnson , ) also finds voice as a foreclosure of fluid possibilities in the lives of fluid people.…”
Section: Foreclosing Fluiditysupporting
confidence: 72%
“…My father rejected me, and I saw my mother's hideously twisted face when I was just fourteen cautiously broaching the topics. This is every day for me.A gender fluid queer wrote about this topic echoing many other respondents and work by Johnson () on the medical experiences of transgender people:
They accuse non‐binary of being special snowflakes, say we're confusing gender and personality, tell us femme is a lesbian only term, but at least they haven't murdered me yet.
Considering the violence enacted upon transgender populations (Stryker ), fluid people, like transgender women and men, confront this possibility (many mentioned it in responses) as a way of dealing with less extreme forms of everyday cisnormativity (see also Schilt and Westbrook for similar). Such efforts both reinforce cisgender norms and foreclose fluid possibility.…”
Section: Foreclosing Fluiditymentioning
confidence: 96%
See 1 more Smart Citation
“…In a parallel, Serano (2007), a transwoman and biologist, provides a scathing critique of sociologists' emphasis on gender as socially constructed, when many transgender people experience gender as internal and intrinsic. In the same vein, a qualitative study found that transgender people appreciate medicalization, because it validates activism (being transgender is not a "choice") and facilitates gender-affirming medical services (Johnson, 2015(Johnson, , 2019). Yet transgender people also report discomfort at the pathologization of inclusion in the DSM, even with the update from "gender identity disorder" to "gender dysphoria" with the DSM-5 (Johnson, 2019).…”
Section: Pride Identity and Activismmentioning
confidence: 99%
“…In the same vein, a qualitative study found that transgender people appreciate medicalization, because it validates activism (being transgender is not a "choice") and facilitates gender-affirming medical services (Johnson, 2015(Johnson, , 2019). Yet transgender people also report discomfort at the pathologization of inclusion in the DSM, even with the update from "gender identity disorder" to "gender dysphoria" with the DSM-5 (Johnson, 2019). Addressing tensions that apply to many DSM diagnoses (e.g., mental illness and learning disabilities), Johnson (2019, p. 529) concludes: "If medicine is to maintain its authority over human problems and its role in finding solutions for those problems, it must expand its models to account for the diverse and polymorphous components of health and wellness or risk promoting partial understandings that eclipse lived experience and prevent comprehensive healing.…”
Section: Pride Identity and Activismmentioning
confidence: 99%